Falling for the lawman - McEwen, Claire (McEwen, Claire. Heroes of Shelter Creek., 2021)
They made a great team...But how long can they last? Shelter Creek deputy Adam Sears wasn't pleased about his temporary new partner. Anxious to catch some poachers, wildlife officer Gracie Long took too many unacceptable risks. Yet after learning Gracie had been through a trauma, Adam was determined to make this relationship work. But as a single father of two young kids, can he trust his family with someone so reckless once the assignment is over?